A Commentary Against Aboriginal to non-Aboriginal Adoption - Richard, Kenn (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2004)
This article focuses on the author’s experience and observations respecting the appropriateness of adopting Aboriginal children into non-Aboriginal settings, and its impact on children, youth and parents receiving services from an Aboriginal child and family services agency in Toronto.